A discussion on the merits and limitations of using drive-by monitoring to detect localised damage in a bridge. (June 2017) - Hester, David; González, Arturo
Highlights: Demonstrates the origin of the damage feature in a vehicle signal due to bridge damage. Provides guidance on how signal processing can be used to capture the damage feature. Examines the limitations of the approach in relation to vehicle speed &road profile. Abstract: Given the large number of bridges that currently have no instrumentation, there are obvious advantages in monitoring the condition of a bridge by analysing the response of a vehicle crossing it. As a result, the last two decades have seen a rise in the research attempting to solve the problem of identifying damage in a bridge from vehicle measurements. This paper examines the theoretical feasibility and practical limitations of a drive-by system in identifying damage associated to localised stiffness losses. First, the nature of the damage feature that is sought within the vehicle response needs to be characterized. For this purpose, the total vehicle response is considered to be made of 'static' and 'dynamic' components, and where the bridge has experienced a localised loss in stiffness, an additional 'damage' component. Understanding the nature of this 'damage' component is crucial to have an informed discussion on how damage can be identified and localised. Leveraging this new understanding, the authors propose a wavelet-based drive-by algorithm. By comparing the effect of the 'damage' component to other key effects defining the measurements such as 'vehicle speed', the 'road profile' and 'noise' on a wavelet contour plot, it is possible to establish if there is a frequency range where drive-by can be successful. The algorithm uses then specific frequency bands to improve the sensitivity to damage with respect to limitations imposed by Vehicle-Bridge vibrations. Recommendations on the selection of the mother wavelet and frequency band are provided. Finally, the paper discusses the impact of noise and road profile on the ability of the approach to identify damage and how periodic measurements can be effective at monitoring localised stiffness changes.